Quantitative ethnopharmacological profiling of medicinal shrubs used by indigenous communities of Rawalakot, District Poonch, Azad Jammu and Kashmir, Pakistan - Hussain,Sajjad (2019)
Abstract This paper presents the first comprehensive report on traditional uses of medicinal shrubs of Rawalakot city, district Poonch, Azad Jammu and Kashmir, Pakistan. Ethobotanical data obtained from 120 informants were analyzed by relative frequency citation, use value, family use value, informant consensus factor, fidelity level and Jaccard index. In total, 41 shrubs belonging to 24 families and 34 genera were documented. Rosaceae was reported the most dominant family in the area (six species) and Berberidaceae showed maximum family use value (0.68). Leaves (35%) and fruits (33%) were the most commonly used plant parts and most of the medicines were prepared in the form of decoction. The high informant consensus factor value (0.94) was recorded for diabetic disease category. Medicinal plants with high fidelity level values (100% each) were Berberis lycium, Cydonia oblanga, Ricinus communis, Ziziphus jujuba and Nerium oleander. Berberis lycium was the most significant shrub in the area with highest use value (0.68). Relative frequency citation value was maximum for Rubus ellipticus (0.30), Nerium oleander and Indigofera heterantha (0.10 each). Percentage of similar plant uses ranged from 21.05 to 0.62% and dissimilarity percentage ranged from 32.50 to 0.66%. Out of the 41 shrub species, six were reported with new therapeutic uses and may represent new bioresources. These were Debregeasia salicifolia (diabetes), Desmodium elegans (anti-cancerous), Hibiscus rosa-sinensis (jaundice), Hypericum oblongifolium (arthritis), Sarcococca saligna (tuberculosis), Rubus niveus (chronic cough) and Otostegia limbata (renal disorders). We suggest that species reported with high use value should be involved in cultivation and agricultural practices for their sustainable use and those reported with new therapeutic uses should be employed in further biotechnological, pharmacological and clinical studies in order to validate their traditional uses.